2016
DOI: 10.1038/srep27892
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility related to enzyme activity: evidence for a dynamic active-site gatekeeper function of Tyr215 in Aerococcus viridans lactate oxidase

Abstract: L-Lactate oxidase (LOX) belongs to a large family of flavoenzymes that catalyze oxidation of α-hydroxy acids. How in these enzymes the protein structure controls reactivity presents an important but elusive problem. LOX contains a prominent tyrosine in the substrate binding pocket (Tyr215 in Aerococcus viridans LOX) that is partially responsible for securing a flexible loop which sequesters the active site. To characterize the role of Tyr215, effects of substitutions of the tyrosine (Y215F, Y215H) were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 54 publications
3
42
0
3
Order By: Relevance
“…As a control we used in-house produced AvLCTO with both affinity tag (tag cleaved later during purification) and tag free version. Both of these versions of AvLCTO had enzymatic activity similar to earlier reports [22]. We also tested other substrates such as glycolate and 4-hydroxy mandelate with PaLCTO but no activity could be seen.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As a control we used in-house produced AvLCTO with both affinity tag (tag cleaved later during purification) and tag free version. Both of these versions of AvLCTO had enzymatic activity similar to earlier reports [22]. We also tested other substrates such as glycolate and 4-hydroxy mandelate with PaLCTO but no activity could be seen.…”
Section: Discussionsupporting
confidence: 76%
“…Recent experimental evidence has shown that Tyr215 controls entry and exit of substrate and product in AvLCTO as mutations in Tyr215 result in a change in time of product release [22]. The corresponding residue in PaLCTO is Tyr214 and due to similarity, the loop could have a similar role in this enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Protein structure analysis indicated that the replacement of Asp501 caused a decrease in the number of hydrogen bonds formed at position 501 and a larger space between Gly501 and Met 503 ( Figure S3), which may increase the conformational flexibility of this region. Conformational flexibility in the active site is important for substrate binding and for enzyme catalysis, and there is usually a positive correlation between conformational flexibility and enzyme activity [24][25][26]. As mentioned above, the Asp501 is adjacent to the axial ligand (Met502) of the T1 copper ion and lies at the surface of the water channel.…”
Section: Indigo Carmine Decolorizationmentioning
confidence: 99%
“…This is achieved by conformational dynamics of the loop. Substitutions in this residue were shown to reduce the rate of product release from the enzyme [12].…”
Section: Introductionmentioning
confidence: 99%